Rancang Bangun Sistem Poskes Berbasis Web Menggunakan Metode Waterfall untuk Memonitoring Kesehatan Masyarakat Desa Kedung Pilang - Fanny Ryan Rizkiansah; Dhefi Intan Lukmana; Muhammad Abdul Aziz (Jurnal Kajian dan Penelitian Umum, 2026)
Advances in digital technology have had a significant impact on the health sector, particularly in the management and monitoring of public health data. However, at the Village Health Post (Poskes) level, paper is still used to record participant data, resulting in frequent recording errors and data loss, as well as delays in monthly reporting. This situation occurs at the Kedung Pilang Village Health Post, which still uses manual methods for recording public health data. This study aims to design a web-based Poskes system to improve the effectiveness of public health services. The system development used the Waterfall method, which includes needs analysis, design, implementation, testing, and maintenance. The system was built using PHP Native and MySQL and tested using the Black Box Testing method. The results of the study indicate that the system is able to simplify the process of recording, storing, searching, and monitoring health data more quickly, structured, and effectively. This system also helps improve the work efficiency of officers and the quality of health services in Kedung Pilang Village.